2009
DOI: 10.2174/1874839200903010024
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Economic Carrying Capacity for an Ungulate Guild in Western Canada

Abstract: Elk Island National Park in western Canada provides an ideal case study for an economic carrying capacity estimate because it supports high density of four species of ungulates (11/km 2 ), lacks large predators, and is enclosed by a 2.1-meter mesh fence. This high density of ungulates has created persistent management challenges by altering vegetation structure and community composition. Using linear programming, we explored optimal allocation of forage resources for bison (Bison bison bison), moose (Alces and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 107 publications
0
10
0
Order By: Relevance
“…Our second goal was to estimate bison carrying capacity given the potential habitat available. We focused on winter under the assumption that this was the season that sets the upper limit on bison population size [ 28 , 29 ]. First, we estimated available forage biomass ( Fig 2 ), then we constrained availability based on grazing intensity, HSI, and the three snow-depth scenarios.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Our second goal was to estimate bison carrying capacity given the potential habitat available. We focused on winter under the assumption that this was the season that sets the upper limit on bison population size [ 28 , 29 ]. First, we estimated available forage biomass ( Fig 2 ), then we constrained availability based on grazing intensity, HSI, and the three snow-depth scenarios.…”
Section: Methodsmentioning
confidence: 99%
“…They used field trials to estimate a refuge for plants of 13% of the standing forage biomass, equivalent to a maximum offtake of 87%. At the lower end of published studies, Kuzyk et al [ 29 ] reported results of carrying capacity estimates for 4 ungulates species in Elk Island National Park using 7–15% forage use for graminoids and forbs, and 60% for shrubs, based on empirical observations in that system. Similarly, Sachro et al [ 62 ] used a grazing intensity of 25% to estimate elk nutritional carrying capacity in Banff.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Estimates of animal carrying capacity (Baars and Jeanes, 1997;Afzal et al, 2007;Savadogo et al, 2007;Chaudhry et al, 2010;Robinson et al, 2010;Hajno and Tahiri, 2011) have been successfully used in management decisions and planning (Mayer et al, 2006) and help to achieve sustainable utilization of ecosystems (Stoddart et al, 1975;Kuzyk et al, 2009). Animal carrying capacity is defined as the maximum stocking rate that a certain land area can support on a sustainable basis during a defined grazing season (FAO, 1991).…”
mentioning
confidence: 99%